The Power Plays of Identities on Commercial Farms in Zimbabwe: "Law and Gender" in Southern Africa Revisited - Rutherford, Blair (Anthropologica, 2022)
This article raises questions about the heuristic and political effects of "normalizing" sociological identities, the state and space through discussing gendered identities on commercial farms in Hurungwe District, Zimbabwe. It discusses how the various "interests" of men and women farm workers cannot be "read" off their gender but must be situated within the jural identities that have emerged within the specific legal space of commercial farms. Through approaching farm workers this way, it is suggested that academic studies and political interventions can better understand the jural identities and power relations involved on the commercial farms and in our own representations.